A doutrina do Higienismo na Revista de Educação e Ensino: Octavio Pires e a higiene dos internatos - Damasceno, Alberto; Pantoja, Suellem; Miranda, Joaquina Ianca (Faculdade de Educação/Universidade Estadual de Campinas, 2021)
This article aims at identifying and comprehending the ideas of Octavio Pires on hygiene in the boarding schools. For this purpose, historical research was developed based on articles published in the Revista de Educação e Ensino, between February and November 1892, by Octavio Pires, who was its director, main columnist and one of the promoters of the higyenism doctrine in Pará. Concerning the treatment of data, we use the technique of content analysis when we notice the strong influence and the constant recurrence to European experiences at that time, constantly quoted as essential references for educational leaders in Pará. We also observe the intervention of hygienist agents in educational productions and practices, not only regarding the definition of physical spaces and program content, but also the teaching methods themselves, prescriptions of “control”, “surveillance” and “inspection” as elements that had constituted the implementation of hygiene in schools, revealing the intense apprehension with discipline and morals.